Awareness of Thyroid Surgeons on Voice and Airway Complications: An Attitude Survey in Turkey - ENVER, NECATİ (MOSBY-ELSEVIER, 2021)
Introduction. Thyroidectomy is one of the most commonly performed surgical procedures. Preoperative patient education and postoperative management of complications are vital to avoid postoperative medicolegal problems. Objective. The aim of this study was to assess the attitudes of thyroid surgeons about voice and airway complications of the surgery and the approaches used to avoid or handle these complications. Methods. A questionnaire based on surgeons' attitudes and behaviors on thyroidectomy was answered by 177 thyroid surgeons. Questions regarding demographic information, preoperative information methods, preoperative laryngeal examination, intraoperative nerve preservation techniques, and methods to avoid and handle postoperative complications were asked. Surgeons who completed the questionnaire were divided into three groups based on their annual volumes: less than 50 (low volume), 50-100 (middle volume), and more than 100 (high volume) for statistical analysis. The differences between the subgroups were compared using the chi-squared test. Results. During the preoperative disclosure, nearly all surgeons (97.2%) gave information about possible hoarseness; however, this high rate fell to 79.7% for possible voice changes, and to the lowest level of 36.7% for ability to change the voice pitch. Only 53.7% of the surgeons discussed the possibility of postoperative tracheostomy requirement. The surgeons with high annual volumes were found to perform vocal fold examination prior to a second surgery significantly higher than other groups (P=0.015). In the postoperative period, 84.2% of physicians indicated that they perform a laryngoscopic examination only for patients with voice problems. There was no statistically important difference between subgroups. Conclusions. Our study is unique to provide information from the surgeons' perspective by evaluating preoperative patient information, and intraoperative and postoperative protective and curative methods. The training of residents and fellows who are expected to perform thyroidectomies can be revised to compromise all aspects of complications.
Keywords: Thyroidectomy; Vocal fold paralysis; Recurrent laryngeal nerve; Intraoperative nerve monitoring; Neck surgery